2005
DOI: 10.1577/t05-037.1
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Environmental Conditions during Stream, Estuary, and Ocean Residency on Chinook Salmon Return Rates in the Skagit River, Washington

Abstract: We predicted 22 years of return rates for wild Chinook salmon Oncorhynchus tshawytscha as a function of environmental conditions experienced during residency in freshwater, tidal delta, bay, and ocean habitats as well as as an indicator of density dependence (based on egg production) across life stages. The best predictors of return rate included the magnitude of floods experienced during incubation, a principal components factor describing environmental conditions during bay residency, a similar factor descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 62 publications
4
74
1
Order By: Relevance
“…Nevertheless, our results consistently showed that in the Lemhi River, flow variables had stronger explanatory power than climate predictors, corroborating some studies that have detected higher covariation in life-cycle production at subbasin rather than basinwide scales (Schaller et al, 1999;Botsford & Paulsen, 2000;Deriso et al, 2001). Studies that have included flow as well as climate signals in the context of the life cycle have also shown strong effects of flow (e.g., Greene et al 2005). Models of single spawning populations with long time series that can disentangle effects of flow from other environmental variables are clearly needed to evaluate the influence of hydromodification against the backdrop of climate variation at multiple life stages.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, our results consistently showed that in the Lemhi River, flow variables had stronger explanatory power than climate predictors, corroborating some studies that have detected higher covariation in life-cycle production at subbasin rather than basinwide scales (Schaller et al, 1999;Botsford & Paulsen, 2000;Deriso et al, 2001). Studies that have included flow as well as climate signals in the context of the life cycle have also shown strong effects of flow (e.g., Greene et al 2005). Models of single spawning populations with long time series that can disentangle effects of flow from other environmental variables are clearly needed to evaluate the influence of hydromodification against the backdrop of climate variation at multiple life stages.…”
Section: Discussionsupporting
confidence: 89%
“…Seiler et al (2003) found that the annual incubation flood magnitude was a significant predictor of freshwater survival rates for Skagit River chinook salmon, wherein larger floods resulted in smaller survival rates. Greene et al (2005) found that the annual flood magnitude was a strong predictor of total lifecycle return rates for Skagit River chinook salmon. These findings could result from several different mechanisms linking peak incubation flows to early freshwater life-stage survival rates for salmon.…”
Section: Model Validation and Applicationmentioning
confidence: 96%
“…This low-level salinity environment (<15 ppt) are very suitable for fish migratory pathways in estuaries [3,26,27] and can increase fish return rate into Skagit River. For example, Greene et al [28] suggested that freshwater and nearshore environmental conditions are the main controlling factors of the survival rate of Skagit River Chinook salmon. …”
Section: Discussionmentioning
confidence: 99%